CT pulmonary angiography in pregnancy: Specific conversion factors to estimate effective radiation dose from dose length product: A retrospective cross-sectional study across a multi-hospital integrated healthcare network. Issue 143 (October 2021) - Cohen, Stuart L.; Wang, Jason J.; Chan, Nicholas; Austin McCandlish, John; Feizullayeva, Chinara; Cronin, Paul P.; Barish, Matthew; O'Connell, William; Sanelli, Pina
Abstract: Purpose: Effective dose describes radiation-related cancer risk from CT scans and is estimated using a readily available conversion factor ( k -factor), which varies by body part and study type. To purpose of this study is to determine the specific k -factor for CTPA in pregnant patients and its predictive factors. Methods: This retrospective cross-sectional study evaluates CTPA in pregnancy across a multihospital integrated healthcare network from January 2012 to April 2017. Patient and CTPA-related data were obtained from the electronic health record and a radiation dose index monitoring system. Each patient's effective dose was determined by patient-specific Monte-Carlo simulation with Cristy phantoms and divided by patient dose-length-product to determine the k -factor. K -factor for pregnant patients was compared to the k -factor for adults of standard physique with a one-sample t -test. Bivariate and multivariable analyses were performed for patient and CT predictors of k -factor. Results: A total of 534 patients were included. The mean k -factor for all patients was 0.0249 (mSv·mGy −1 ·cm −1 ), 78% greater than k -factor of 0.014 (p < 0.001) suggested for the general adult population. Multivariable analysis demonstrated lower k -factors with increasing pitch (p = 0.0002), patient size (p < 0.001), and scan length (p < 0.0001). The 120 kVp (p < 0.001) and 140 kVp (p = 0.0028) analyses showed a larger k -factor than 80 and 100 kVp studies combined. Conclusions: Specific k -factor for CTPA in pregnant patients is greater than the previously used generic chest CT k- factor and should be used to estimate the effective dose for CTPA exams in pregnancy.